A Three-year Follow-up of Intravitreal Triamcinolone Acetonide Injection and Macular Laser Photocoagulation for Diffuse Diabetic Macular Edema - Cho, Hee Yoon (The Korean Ophthalmological Society, 2012)
PURPOSE: To report the three-year outcomes of macular laser photocoagulation following intravitreal injection of triamcinolone acetonide (IVTA) for diffuse diabetic macular edema (DME). METHODS: A prospective, randomized controlled study was completed. Eighty-six eyes of 74 patients with diffuse DME were randomized into two groups. Eyes assigned to the combination group (n = 48) were subjected to macular laser photocoagulation three weeks after IVTA. Eyes in the IVTA group (n = 38) underwent IVTA alone. Central macular thickness was measured by optical coherence tomography, and the number of additional treatments and mean time to recurrence were assessed. RESULTS: Thirty-seven eyes in the combination group and 26 eyes in the IVTA group completed the three-year follow-up. Recurrence of DME after initial treatment was not observed for nine of the 37 (24.3%) eyes in the combination group or for one of the 26 (3.9$) eyes in the IVTA group (p = 0.028). DME was absent for 19.9 months after treatment in the combination group compared to 10.3 months in the IVTA group (p = 0.027). The mean number of additional treatments was 0.92 in the combination group and 1.88 in the IVTA group (p = 0.001). CONCLUSIONS: Results in the subset of subjects who completed the three-year follow-up demonstrated that laser photocoagulation following IVTA is more effective than IVTA monotherapy for diffuse DME. Combination therapy required fewer additional treatments and resulted in a lower recurrence rate than IVTA monotherapy.